2008
DOI: 10.1073/pnas.0803004105
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability of white matter towards antenatal hypoxia is linked to a species-dependent regulation of glutamate receptor subunits

Abstract: White-matter damage is a leading cause of neurological handicap. Although hypoxia-ischemia and excitotoxicity are major pathogenic factors, a role for genetic influences was suggested recently. Thus, protracted gestational hypoxia was associated with whitematter damage (WMD) in rat pups but not in mouse pups. Indeed, microglial activation and vessel-wall density on postnatal days (P)1 and P10 were found increased in both mouse and rat pups, but cell death, astrogliosis, and myelination were only significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 46 publications
(55 reference statements)
1
26
0
Order By: Relevance
“…As previously reported, antenatal hypoxia induced a significant decrease in density of MBP-positive fibers in both the cingulum and striatum [9,11]. Our data showed that postnatal hyperoxia was associated with a significant decrease in myelin content in cingulate white matter at P10 (p < 0.05 vs. controls).…”
Section: Resultssupporting
confidence: 76%
“…As previously reported, antenatal hypoxia induced a significant decrease in density of MBP-positive fibers in both the cingulum and striatum [9,11]. Our data showed that postnatal hyperoxia was associated with a significant decrease in myelin content in cingulate white matter at P10 (p < 0.05 vs. controls).…”
Section: Resultssupporting
confidence: 76%
“…Nonspecific background densities were measured at each brain level in a region devoid of MBP or NG2 immunolabeling and were subtracted from values of the region of interest as previously reported [18]. …”
Section: Methodsmentioning
confidence: 99%
“…[16][17][18][19][20][21] Genetic factors have also been shown to influence the developing brain's response to sensitizing factors. 22,23 Robust epidemiological studies, performed in preterm and term-born neonates, support a role for inflammation as a sensitizer. These studies suggest a strong association between fetal infection and inflammation (e.g.…”
Section: Concept Of Inflammation-induced Sensitizationmentioning
confidence: 99%